Distribution network reconfiguration with distributed power based on genetic algorithm - Yao Shu-jun; Yan Zhi; Wang Yan; Yan Yu-xin; Song Xiao-yan (2011 4th International Conference on Electric Utility Deregulation and Restructuring and Power Technologies, 2011)
This paper focuses on distributed power(DG) impact on distribution network and distribution network reconfiguration algorithms. First the article describes the impact of DG on distribution networks failure reconfiguration, Then set reconfiguration evaluation model based on Wind turbine as a specific DG, based on the above, adjust the fitness function structure of Improved genetic algorithm. Meanwhile, this selection operator using the tournament selection method combined with elitist selection method approach in order to make the Selection operator of genetic algorithm focus on the fitness value compared and keep high fitness individuals. Finally, test examples show that the algorithm is reasonable and effective.